Comparison of Parenting Stress in Mothers of Children with Cancer - Fatemeh Hashemi; Sarah Sepahvand; Mojtaba Habibi Asgarabad; Marzeyeh Ganjavi; Mahtab Mirzaee (Shahid Beheshti University of Medical Sciences, 2018)
Background and Objectives: Cancer in the child is considered as a traumatic event for parents, and immediately after the diagnosis of a child's disease, parents, especially the mother, experience extensive stress that causes psychological adjustment problems. The purpose of this study was to compare maternal stress subscales of mothers with children who are suffering from cancer, by gender, education, occupation and parents' disease. Material and Methods: This descriptive correlational study was conducted with the participation of 300 mothers with a child with cancer under the age of 18 years who were not selected randomly using available sampling method. Mothers completed Abidin Parenting Stress questionnaire for collecting information. Data were analyzed using SPSS-21 software and descriptive and inferential statistics (Pearson correlation coeffiient and multivariate analysis of variance analysis). Results: The mean (SD) of the expectations of children with cancer without a history of parental disease was 25.2 (5.1) and more than the expectations of children with cancer with a history of parental disease 23.5 (5.1), and the overall health status of mothers without a history of disease was 23.5 (5.1) more than mothers with a history of disease 9.3 (2.9) (P<0.001). The hyperactivity and lack of attention in boys with a mean (SD) of 22.7 (6.8) were more than girls 21.6 (6.2) (P<0.05), and girls experienced a higher incidence of depression 26.2 (7.5) during disease compared to boys 24.2 (6.6) (P<0.05). Conclusion: The age and sex of the child, the age of the father, the status of mother's employment and the history of parental disease are factors affecting the level of perceived parenting stress by mothers with children with cancer.